CREATING ECO-FRIENDLY ARTWORKS THROUGH ECOPRINT TECHNIQUE TRAINING USING NATURAL MATERIALS AT THE CENTRAL KARANG ORPHANAGE - Agung Wahyu Hidayat; Deni Faslah; Emilia Putri Nur Aisyiah; Joti Sumitra Dewi; Muhammad Radi; Nur Barizah; Sartika Purnamasari; Zainal Zainal; Putri Kornelia (LPPM STAI Muhammadiyah Probolinggo, 2025)
This community service activity aims to improve the creative skills and environmental awareness of the children of the Central Karang Orphanage through training in ecoprint techniques using natural materials. The implementation method uses the 5-D BAGJA approach based on Asset-Based Community Development (ABCD) which includes the stages of Define, Dream, Design, Deliver, and Destiny. The training was carried out with participatory methods in the form of socialization, demonstrations, and direct practice of making ecoprints on tote bag fabric. The results of the activity showed an increase in participants' understanding of the concept of ecoprint and the importance of using natural materials. Most children are able to produce one to two leaf-patterned works with good aesthetic quality and show high enthusiasm. This activity also fosters awareness of environmental conservation and the potential of the creative economy based on environmentally friendly products. This training has proven to be effective in integrating aspects of art, education, and community empowerment in a sustainable manner.